2010
DOI: 10.1007/s10499-010-9360-5
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of hepatopancreatic and extracellular digestive proteinases of wild and cultivated Octopus maya

Abstract: Proteinases from hepatopancreas (HP) and gastric juice (GJ) from wild and cultured red octopus (Octopus maya) were characterized. Hepatopancreas assays revealed optimal activity at pH 4, 9-10 and 10 for wild and pH 3, 8, and 9, for cultured octopuses, for total proteinases, trypsin and chymotrypsin, respectively. In the gastric juice, maximum activity was recorded at pH 6, 8, and 7 for total proteinases, trypsin, and chymotrypsin, respectively for both wild and cultured octopus. A reduction on enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 30 publications
6
43
0
Order By: Relevance
“…Acidic proteases were several times more active than alkaline proteases in O. maya and O. mimus. This finding supports previous studies suggesting that the main role of acidic protease (presumably cathepsines) in octopus digestion is as extracellular digestive protease (Martínez et al 2011a(Martínez et al , 2012. We observed that GJ enzyme activity in O. maya exhibited several peaks throughout the digestive process, indicating that the release of digestive enzymes from the DG occurred in 2 pulses (Semmens 2002, Martínez et al 2012.…”
Section: Intracellular Digestionsupporting
confidence: 92%
See 4 more Smart Citations
“…Acidic proteases were several times more active than alkaline proteases in O. maya and O. mimus. This finding supports previous studies suggesting that the main role of acidic protease (presumably cathepsines) in octopus digestion is as extracellular digestive protease (Martínez et al 2011a(Martínez et al , 2012. We observed that GJ enzyme activity in O. maya exhibited several peaks throughout the digestive process, indicating that the release of digestive enzymes from the DG occurred in 2 pulses (Semmens 2002, Martínez et al 2012.…”
Section: Intracellular Digestionsupporting
confidence: 92%
“…Activity of total acidic proteinases was evaluated using Stauffer's universal buffer (Stauffer 1989) prepared at pH 6 for GJ samples and pH 3 for DG samples (Martínez et al 2011a). Acidic proteinase and alkaline proteinase activities were assayed using hemoglobin (1%) or casein (1%) as the substrate (Anson 1938).…”
Section: Chyme Digestive Tract Sampling and Enzymatic Activitymentioning
confidence: 99%
See 3 more Smart Citations